Circ-SIRT1 inhibits cardiac hypertrophy via activating SIRT1 to promote autophagy - Wang, Weichen; Wang, Longlong; Yang, Mengyue; Wu, Chunwei; Lan, Rui; Wang, Weiwei; Li, Yuze (Cell death & disease, 2021)
Mounting studies have substantiated that abrogating autophagy contributes to cardiac hypertrophy (CH). Sirtuin 1 (SIRT1) has been reported to support autophagy and inhibit CH. However, the upstream regulation mechanism behind the regulation of SIRT1 level in CH remains unclear. Circular RNAs (circRNAs) are vital modulators in diverse human diseases including CH. This study intended to investigate the regulatory mechanism of circRNA on SIRT1 expression in CH. CH model was established by angiotensin II (Ang II) fusion or transverse aortic constriction (TAC) surgery and Ang II treatment on hiPSC-CMs and H9c2 cells in vitro. Our results showed that circ-SIRT1 (hsa_circ_0093884) expression was downregulated in Ang II-treated hiPSC-CMs, and confirmed that its conserved mouse homolog circ-Sirt1 (mmu_circ_0002354) was expressed at low levels in Ang II-treated H9c2 cells and TAC-induced mice model. Functionally, circ-SIRT1/circ-Sirt1 attenuated Ang II-induced CH and induced autophagy in hiPSC-CMs and H9c2 cardiomyocytes. Mechanistically, circ-SIRT1 could upregulate its host gene SIRT1 at the post-transcriptional level by sponging miR-3681-3p/miR-5195-3p and stabilized SIRT1 protein at the post-translational level by recruiting USP22 to induce deubiquitination on SIRT1 protein. Further, SIRT1 knockdown could rescue the effect of circ-SIRT1 upregulation on Ang II-induced CH and autophagy in vitro and in vivo. In conclusion, we first uncovered that circ-SIRT1 restrains CH via activating SIRT1 to promote autophagy, indicating circ-SIRT1 as a promising target to alleviate CH.